Plants as potential repellent against oryzaephilus species - Abdul, Nurul Huda; Zakaria, Nor Hafizah; Ibrahim, Maizatul Akma (International Society of Academicians, 2019)
Stored food pests are a perennial problem in storage facilities and retail stores where they infest and contaminate on a variety of products including grain products, dried fruits, nuts, seeds, dried meats, and in fact, almost all plant products that were used as human foods. The utilization of synthetic pesticides as the main strategy to control food pests has long attracted major concern due to the residue problems and adverse effects to consumers. In view of the above, there is an increasing extensive search for plant species that are showing insecticidal and repellent properties to eradicate these pests that feed on the stored products. These harmful pests include Oryzaephilus surinamensis Linnaeus which is the subject of this review. This review describes the biology of O. surinamensis L. and summarizes on the current state of the alternative methods using plant as a repellent to control this species and other stored product pests within the same niche.